2015
DOI: 10.1007/s11845-015-1394-2
|View full text |Cite
|
Sign up to set email alerts
|

Post-chemotherapy retroperitoneal lymph node dissection in the management of metastatic testis cancer: the 16-year experience in an Irish setting

Abstract: In this relatively small series due to small population and low disease incidence, we have shown acceptable peri-operative course, morbidity and oncological outcomes with PC-RPLND compared to major international centres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
8
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 24 publications
(25 reference statements)
6
8
0
3
Order By: Relevance
“…No patients died within 30 days and the highest reported Clavien–Dindo grade was IIIb with a frequency of 1.5%. This compares well with other contemporary series that show higher grade complications (Clavien–Dindo Grade III–IV) of 8.9% and overall complication rates of up to 9% . We acknowledge that there may have been variability in case selection, including the potential for a small number of men to have been deemed inoperable.…”
Section: Discussionsupporting
confidence: 82%
“…No patients died within 30 days and the highest reported Clavien–Dindo grade was IIIb with a frequency of 1.5%. This compares well with other contemporary series that show higher grade complications (Clavien–Dindo Grade III–IV) of 8.9% and overall complication rates of up to 9% . We acknowledge that there may have been variability in case selection, including the potential for a small number of men to have been deemed inoperable.…”
Section: Discussionsupporting
confidence: 82%
“…Nakamura et al 25 and Alanee et al 26 reported a probability of 9.0% and 43% for the presence of viable tumors, respectively, while several other studies have also reported viable tumors in 10%-40% of patients. [21][22][23][24][25][26][27] In our study, the frequency of viable tumors was 19.2%, similar to that observed in previous studies. Compared to earlier studies, recent studies have shown that the percentage of patients with residual cancer after chemotherapy has declined, which could potentially be related to the improved efficacy and delivery of chemotherapy.…”
Section: Resultssupporting
confidence: 92%
“…With respect to complications associated with RPLND after chemotherapy, Baniel et al 20 and Considine et al 21 reported complication rates of 18% and 29.5%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations